Involvement of nitric oxide on bothropoides insularis venom biological effects on murine macrophages in vitro - De Menezes, Ramon R.P.P.B.; Mello, Clarissa P.; Lima, Dânya B.; Tessarolo, Louise D.; Sampaio, Tiago Lima; Paes, Lívia C.F.; Alves, Natacha T.Q.; Assis, Eudmar M.; Lima, Roberto C.P.; Toyama, Marcos H. [UNESP]; Martins, Alice M.C. (Public Library of Science (PLoS), 2016)
Viperidae venom has several local and systemic effects, such as pain, edema, inflammation, kidney failure and coagulopathy. Additionally, bothropic venom and its isolated components directly interfere on cellular metabolism, causing alterations such as cell death and proliferation. Inflammatory cells are particularly involved in pathological envenomation mechanisms due to their capacity of releasing many mediators, such as nitric oxide (NO). NO has many effects on cell viability and it is associated to the development of inflammation and tissue damage caused by Bothrops and Bothropoides venom. Bothropoides insularis is a snake found only in Queimada Grande Island, which has markedly toxic venom. Thus, the aim of this work was to evaluate the biological effects of Bothropoides insularis venom (BiV) on RAW 264.7 cells and assess NO involvement. The venom was submitted to colorimetric assays to identify the presence of some enzymatic components. We observed that BiV induced H2O2 production and showed proteolytic and phospholipasic activities. RAW 264.7 murine macrophages were incubated with different concentrations of BiV and then cell viability was assessed by MTT reduction assay after 2, 6,12 and 24 hours of incubation. A time- and concentration-dependent effect was observed, with a tendency to cell proliferation at lower BiV concentrations and cell death at higher concentrations. The cytotoxic effect was confirmed after lactate dehydrogenase (LDH) measurement in the supernatant from the experimental groups. Flow cytometry analyses revealed that necrosis is the main cell death pathway caused by BiV. Also, BiV induced NO release. The inhibition of both proliferative and cytotoxic effects with L-NAME were demonstrated, indicating that NO is important for these effects. Finally, BiV induced an increase in iNOS expression. Altogether, these results demonstrate that B. insularis venom have proliferative and cytotoxic effects on macrophages, with necrosis participation. We also suggest that BiV acts by inducing iNOS expression and causing NO release.